Executive compensation and takeovers : impact of CEO's psychological and biological characteristics on risk-taking and performance - Huang, Jian (Cranfield University, 2007)
This thesis explores the issues surrounding the relation between executive compensation and corporate acquisitions. Based on a sample of 2527 acquisitions in the US from 1993 to 2004, I find that equity-based compensation provides strong incentives for managers to undertake risky acquisitions. Increase in risk change is associated with increase in the sensitivity of CEO wealth to stock return volatility (Vega). Further, higher level of risk change intensifies the positive impact of Vega and the negative impact of the sensitivity of CEO wealth to stock price (Delta) upon acquisition performance. Different from conventional wisdom, the empirical evidence suggests that managerial overconfidence provides an alternative solution to the underinvestment problem induced by managerial risk aversion. Considering the gender, I find that the market has more favourable response to the acquisitions led by female CEOs than those conducted by their male counterparts. However, in the long run, this difference vanishes. Furthermore, risky corporate acquisitions led by female CEOs destroy shareholder's value in the long run. Finally, female CEOs are more responsive to the risk incentive than the male CEOs are. Considering the impact of corporate acquisitions on executive compensation, I find that, after a completed acquisition, CEOs in the firms with stronger managerial power experience increase in cash compensation and decrease in stock grant. Corporate governance does matter. In the firm with stronger corporate governance provisions, i.e., weaker managerial power, CEOs are penalized for poor acquisition performance with decline in cash based compensation. Regarding the direct modelling of endogeneity, Simultaneous equations modelling yields empirical results that are consistent with those generated by Ordinary least squares regression. The analyses of the serial acquisitions sample confirm the general wisdom that executive compensation increases after each deal in an acquisition series. In tum,. executive compensation and its recent increment have certain predictive power over the occurrence of future acquisition activities. Considering performance, after controlling for deal characteristics, I find no significant difference between serial acquirers and occasional acquirers in performance during deal announcement period. In the long run, however, serial acquirers outperform occasional acquirers. Finally, I find no significant relation between levels of executive compensation and serial acquirer's acquisition performance. My empirical analyses suggest that CEO's psychological and biological characteristics need to be taken into account while designing executive compensation. Moreover, my research sheds light on the debate about pay-for-performance relation by empirically showing that executive compensation is at best a two-edged sword. In the case of corporate acquisitions, ex-ante executive compensation can be designed as a corporate governance device to realign the diverged interests between management and shareholders. Nonetheless, executive compensation can potentially become an agency problem as CEOs may engage in corporate acquisition for their own interests but not for those of the shareholders. This agency problem could be more severe in serial acquisitions.